Management of oral medicine emergencies during COVID-19: A study to develop practise guidelines - Na Lv; Ming Sun; Ajith Polonowita; Li Mei; Guangzhao Guan (Elsevier, 2021)
Coronavirus disease (COVID-19) pandemic has become a significant global public health concern. Since the announcement of the Public Health Emergency of International Concern, many countries have implemented lockdown and restrictive quarantines; therefore, routine dentistry, as well as oral medicine practise, have been suspended in several countries. However, urgent oral cares and emergencies are still operated and delivered by on-call dental practitioners. The objective of this study was to investigate the management of oral medicine emergency during a viral pandemic such as COVID-19. During the lockdown period, digital technologies, such as video conferencing with Zoom, Google Meeting or WhatsApp, are useful and efficient tools that oral medicine practitioners could consider to use for patient triage, managing emergencies, reassure, and follow patients remotely. Oral medicine emergencies can be carefully evaluated and triaged via video conferencing and sometimes phone contact, to avoid life-threatening risks while realising the limitations by both patient and clinician.